The impact of structured healthy lifestyle program among type 2 diabetic patients in Kelantan - Ismail, Ab. Aziz al-Safi; Mohamed, Mafauzy; Sulaiman, Suhaiza (2001)
A non-randomised control trial was conducted with the aim to assess the impact of structured healthy life-style program among Type 2 diabetic patients in Kelantan.One hundred and forty Type 2 diabetic patients from Selising Health Centre (inteivention group) and Gaal Health Centre (control group) in Pasir Puteh District were selected using multistage sampling technique.An intervention group was given a structured health education on self-care,dietary advise and exercise.The control group was given conventional health education.Data were collected using a structured questionnaire, anthropometries measurement and blood sampling for random blood sugar and HbAlc. Statistical Package for Social Science (SPSS) version 9.0 was used for analysing the data. The patients in both health centres had a similar sociodemographic distribution (p value > 0.05).Most of them are Malay(99%),females(59% intervention,66%control), married (74% intervention,86% control),and a non-smoker (67% intervention,73% control). Their mean(+SD)age was 56:0 + 10.17 year (intervention) vs 54.2 + 11.75 year (control) and mean (SD) duration of diabetes was 5.6(4.81) year (intervention) vs. 5.4(4.23) year (control).The intervention group showed a significant improvement in mean score of ·knowledge (16.5 (4.49) vs 23.8 {1.42)),practice (14.5(2.13) vs. 15.6 (2.42)), HbAlc (10.3{2.85) vs 8.9(1.93)) and BMI level (26.1(4.08) vs 25.8(3.98)) kgm-2 after the intervention program whereas no significant different seen in the control group.The study showed that the blood glucose control and BW of Type 2 diabetic patients could be improved if they are willing to change their lifestyle.The main challenge in management of these patients is however to sustained their healthy lifestyle.